2011
DOI: 10.1073/pnas.1100186108
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Bacterial persistence by RNA endonucleases

Abstract: Bacteria form persisters, individual cells that are highly tolerant to different types of antibiotics. Persister cells are genetically identical to nontolerant kin but have entered a dormant state in which they are recalcitrant to the killing activity of the antibiotics. The molecular mechanisms underlying bacterial persistence are unknown. Here, we show that the ubiquitous Lon (Long Form Filament) protease and mRNA endonucleases (mRNases) encoded by toxin-antitoxin (TA) loci are required for persistence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
557
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 459 publications
(599 citation statements)
references
References 56 publications
30
557
3
3
Order By: Relevance
“…Ectopic overexpression of ribonucleases (RelE and MazF toxin), HipA (a glutamyl transfer RNA synthetase protein kinase) and TisB (membrane damage protein) enhances drug tolerance in bacteria 39,[62][63][64] . In E. coli, TA systems function synergistically, and the successive deletion of 10 TA systems progressively reduces persister cell formation in vitro 8 . In this study, we observed that MazEF TA systems are differentially induced in Mtb persisters, and simultaneous deletion of MazF3, MazF6 and MazF9 significantly reduced persister cell formation in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ectopic overexpression of ribonucleases (RelE and MazF toxin), HipA (a glutamyl transfer RNA synthetase protein kinase) and TisB (membrane damage protein) enhances drug tolerance in bacteria 39,[62][63][64] . In E. coli, TA systems function synergistically, and the successive deletion of 10 TA systems progressively reduces persister cell formation in vitro 8 . In this study, we observed that MazEF TA systems are differentially induced in Mtb persisters, and simultaneous deletion of MazF3, MazF6 and MazF9 significantly reduced persister cell formation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…TA systems are widespread in bacterial genomes and contribute to prokaryotic stress adaptation and the formation of persister cells and biofilms 1,[7][8][9] . The toxin components of the TA modules exert their effects in different ways by targeting essential cellular functions such as DNA replication, protein synthesis, cell division, peptidoglycan biosynthesis and ribosome assembly; however, RNA cleavage is the most prevalent mode of action [10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…7,12,31,32 Although TAs are key players in adjusting physiology during adaptation processes, how bacteria coordinate their expression individually and as a whole set remain poorly understood. 15,[33][34][35][36][37] In particular, a limited number of studies have focused on putative crosstalks between TAs. For instance in E. coli, the TA-II endoribonuclease toxin MsqR was shown to enhance a selective degradation of the ghoST mRNA in favor of the type V TA toxin GhoT, by direct cleavage within the ghoS sequence and, a complex regulatory interplay has been unveiled between several TA-II modules.…”
Section: Introductionmentioning
confidence: 99%
“…Numbers on the x-axis refer to the number of TA loci that were deleted in the strains tested. Adapted from Maisonneuve et al [35].…”
Section: Control Of Persistence By Type II Toxinantitoxin Modulesmentioning
confidence: 99%